PERAN SERTIFIKAT TANAH SEBAGAI AGUNAN KREDIT DI BANK DALAM MENINGKATKAN AKSES PERMODALAN DAN INVESTASI USAHA - Loso Judijanto (BORJUIS: JURNAL OF ECONOMY, 2025)
Access to capital is a crucial factor for business growth and sustainability, especially in the Micro, Small and Medium Enterprises (MSME) sector, which often faces obstacles in obtaining financing from formal financial institutions. Land certificates, as proof of legal ownership and having a relatively stable economic value, play a strategic role as collateral for bank loans, which can increase banks' confidence in lending. This study aims to analyse the role of land certificates as collateral in supporting access to capital and its impact on business investment. The method used is library research with a descriptive-qualitative approach, using data sources from academic literature, legislation, financial institution reports, and relevant previous research results. The analysis results indicate that the use of land certificates as collateral can expand access to capital for business actors, enable financing with more competitive amounts and tenors, and encourage an increase in productive investment such as the acquisition of fixed assets, increased production capacity, and market development. However, its effectiveness is influenced by external factors such as economic conditions, land disputes, and the level of legal and financial literacy. Optimising the role of land certificates requires policy support, improved business management capacity, and synergy among stakeholders so that the benefits can be felt in a sustainable manner.